Analytical and Optimization Study of Propagation and Reduction of Wave in Granular Sand by DEM Method - Petrudi, Amin Moslemi; Rahmani, Masoud (European Journal of Computational Mechanics, 2021)
In this research, the discrete element method has been used to analyze wave propagation and to investigate the factors affecting wave reduction in granular soils. The method of discrete elements is important because of the possibility of preparing completely similar specimens and examining the effect of changes in a certain parameter on the Behavior of the specimens. This method also provides an understanding of the changes that have occurred at the micro-scale of granular materials that are not achievable with other laboratory and numerical methods. To model the specimens, a set of disks with specific granulation has been used for two-dimensional studies. PFC 2D software has been used to perform simulations and related analyzes such as interparticle force. The DEM code in MATLAB is used to check the wave depreciation. In this research, the optimization process was performed using experimental data and the Taguchi method using the DEM method. The results of this study show that there is a direct relationship between the number of particle set contacts and the wave propagation speed. Also, material properties such as particle density are the most important parameters affecting wave velocity. The results of the method (DEM) are done with PFC 2D software and a comparison between the results of this method with the solution methods used by other researchers is shown to be a good match.